The Influence of HDI, Per Capita Income, Population Growth on Poverty on Java Island in 2017-2022 with Zakat as a Moderating Variable - Naini, Dani Esti; Bawono , Anton (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
This research aims to determine the effect of the Human Development Index, Per Capita Income, and Population Growth on Poverty on Java Island in 2017-2022 with Zakat as a Moderating Variable. This type of research is quantitative research with a population, namely the Province of Java Island. Meanwhile, the sample for this research was determined using the Saturated Sampling method with criteria determined by the researcher so that a sample of 36 samples from 6 provinces were obtained during the observation period (2017-2022). The type of data used is panel data. The analytical methods used include descriptive tests, statistical tests, stationary tests, multiple regression tests, T-tests, F tests, R² tests, classical assumption tests, and MRA tests. The Moderated Regression Analysis (MRA) test uses Eviews 10 data processing software. The results of the research partially show that the Human Development Index variable has a negative and significant effect on poverty and Per Capita Income has a negative and significant effect on poverty. Based on the Moderated Regression Analysis (MRA) test, shows that the interaction of Zakat is unable to moderate the influence of the Human Development Index, Per Capita Income, and Population Growth.